Security of employment in Malaysia with special reference to the federal constitution - V. Sreedaran Nair, Veloo Pillay (2018)
This study explains and expends the meaning of livelihood and employment under the liberal definitions of the various Articles in the Federal Constitution of Malaysia. It also points out the need to fall back on the Federal Constitution as the last bastion to safeguard the employments of workmen in Malaysia from unconscionable actions of some employers. More than 88% percentage of awards handed down by the Industrial Courts from the years 2005 to 2017 is in the category of dismissal; it is a cause for concern and very worrisome trend in terms of protection of employment. This research looks at how the Federal Constitution can be utilized and interpreted broadly to afford additional protection to fellow workmen from dismissal including dismissal due to whistle-blowing activities. It is with fervent hope that with proper and appropriate judicial interpretation of the Federal Constitution, the applicability of it can be further extended to include protection of right to livelihood in Malaysia. With the decided employment law authorities, it is found that the expansion on the relevant articles of the Federal Constitution has achieved the intended purpose of the utilization of the supreme law to protect the legitimate interest and expectations of employees. The current regimes of the Acts of parliaments such as Employment Act 1955 and Industrial Relations Act 1967 can be further empowered and enhanced in their quests to protect the legitimate interest of workmen. Findings from this study’s case laws and authorities infer that the synergy between the Federal Constitution and Employment Act 1955 and Industrial Relations Act 1967 can provide padded protection to the fellow workmen to safeguard their livelihoods from the unscrupulous conducts of the employers. It is also found that since the case of Tan Teck Seng in 1996 onwards, the Industrial Courts and higher courts in Malaysia were daring enough to apply the wide interpretations of the Fundamental Liberties to provide the constitutional protection to workmen in Malaysia.